Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0208608
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for efficacy and safety in refractive surgery for myopia

Abstract: PurposeTo evaluate the predictive factors for safety and efficacy in laser refractive surgery for myopiaSettingA singular refractive surgery center, at a University-affiliated tertiary medical center.DesignRetrospective cohort studyMethodsStudy population—A total 8,775 eyes having laser refractive laser procedures for myopia (in4,623 patients).Observation procedures–Using a prospective database of refractive procedures performed over the span of 13 years, variables such as gender, age, type of surgery, date of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…The mean residual refractive target after ICL implantation (−0.51 ± 1.12 D) falls within a range that guarantees precise correction with an excimer-based approach. 18 , 19 In a retrospective comparative study between TICL implantation and bioptics for high myopic astigmatism, Alfonso et al 20 demonstrated that bioptics were more likely to achieve MSE within 0.50 D (94% vs 81%) at 12-month postoperatively. Postoperative UDVA was also twice as likely to meet or exceed preoperative CDVA (57.8% vs 32.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The mean residual refractive target after ICL implantation (−0.51 ± 1.12 D) falls within a range that guarantees precise correction with an excimer-based approach. 18 , 19 In a retrospective comparative study between TICL implantation and bioptics for high myopic astigmatism, Alfonso et al 20 demonstrated that bioptics were more likely to achieve MSE within 0.50 D (94% vs 81%) at 12-month postoperatively. Postoperative UDVA was also twice as likely to meet or exceed preoperative CDVA (57.8% vs 32.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Myopia was grouped as mild (MRSE is between 0 and −3.00 D), moderate (MRSE is between −3.01 D and −6.00 D), and high (MRSE is -6.01 D and above). [ 12 ] A total of 115 eyes of 59 patients were included among which 67 eyes underwent t-PRK and 48 eyes underwent PRK.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the most commonly used local treatments for this tumor are brachytherapy (iodine-125, ruthenium-106, or palladium-103, or cobalt-60) and teletherapy (proton beam, helium ion, or stereotactic radiosurgery using a cyber knife, gamma knife, or linear accelerator); the alternative to radiation is eye enucleation [24,25]. In this context, uveal melanoma cells offer an excellent biological environment to study due to the ubiquitous use of NIR CW and pulse lasers in multiple types of eye surgery [26][27][28].…”
Section: Introductionmentioning
confidence: 99%